Anthropometric characteristics and physiological responses of high level swimmers and performance in 100 m freestyle swimming - Rozi, G.; Thanopoulos, V.; Geladas, N.; Soultanaki, E.; Dopsaj, M. (Movement & Sport Sciences - Science & Motricité, 2018)
The effect of the anthropometric characteristics on performances has been the subject of many studies (Reilly, T., Bangsbo, J., & Franks, A. (2000). Anthropometric and physiological predispositions for elite soccer. Journal of Sports Science, 18(9), 669-683) but performance also depends on different physiological parameters. The aim of the present study is to define the anthropometric and physiological variables that best predict performance time of 100 m freestyle swimming. Twenty-five competitive male swimmers (age: 15 ± 1.2 years) participated in the research. Multiple stepwise regression analysis showed that arm span is the best predictor of 100 m freestyle swimming performance (r = 0.835). Arm span explains 68.5% of the variance of dependent variable (Adj R2: 0.685). In the final model, the variables that best describe 100 m freestyle swimming are the number of strokes of 100 m freestyle swimming, triceps skinfold, pelvis and shoulders width (Adj R2: 0.882). These findings confirm the importance of the anthropometric variables for swimming performance and could help coaches in the selection of high-level athletes.